2016
DOI: 10.1007/s40520-016-0591-9
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status, physical performance and disability in the elderly of the Peruvian Andes

Abstract: Poor nutritional status was found significantly associated with poor physical performance and poor functional status in elderly Peruvian individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…Therefore, results may provide evidence for further investigation into the impact of malnutrition on discrete measures of muscle power as the physical performance tests in the current study involve multiple systems and muscle functions. Our study confirms the previously reported associations between malnutrition and CST, gait speed, TUG, and SPPB Score [25][26][27][28][29][30][31][32], with the added novel component of comparing the effects of the associations. We expected that malnutrition would show the strongest association with HGS as a direct measure of muscle function, i.e., strength.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, results may provide evidence for further investigation into the impact of malnutrition on discrete measures of muscle power as the physical performance tests in the current study involve multiple systems and muscle functions. Our study confirms the previously reported associations between malnutrition and CST, gait speed, TUG, and SPPB Score [25][26][27][28][29][30][31][32], with the added novel component of comparing the effects of the associations. We expected that malnutrition would show the strongest association with HGS as a direct measure of muscle function, i.e., strength.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, a recent systematic review conducted by Correia, Perman, and Waitzberg (2017) pointed to a high prevalence of malnutrition among patients undergoing abdominal surgery (61.5%), colon surgery (63.6%), and hernia surgery (55%). Previous studies suggest that older people's nutritional status influences their functional capacity (Abd-Al-Atty et al, 2012;Tramontano et al, 2016). In this study, the MNA-SF scores had a greater statistically significant correlation with the BI scores than with the LBS scores.…”
Section: Discussionmentioning
confidence: 41%
“…Souza et al (2015) concluded that older people's independence to perform basic and instrumental activities of daily living was associated with a healthy weight. Similarly, Tramontano et al (2016) reported that the physical performance and functional status of older people were significantly associated with their nutritional status. In a study conducted with 230 older adults who had been recently hospitalized, Abd-Al-Atty, Abou-Hashem, and Elaziz (2012) reported that the nutritional status, which was assessed using the Mini Nutritional Assessment -Short Form (MNA-SF) and biochemical markers, was an important risk factor for the decline in the functional capacity to perform both activities of daily living (ADL) and instrumental activities of daily living (IADL).…”
Section: Introductionmentioning
confidence: 96%
“…Among a total of 1501 participants, we excluded those who had missing data for RFS ( n = 166), physical performances ( n = 265), and the covariates ( n = 84). We also excluded subjects who had musculoskeletal disorders ( n = 364), such as osteoarthritis, osteoporosis, backache, sciatic neuralgia, and herniated cervical disc, based on the fact that these subjects were also excluded in other studies that examined the association between diet and physical performance [16, 35, 36]. Finally, 622 subjects (294 men and 328 women) aged over 65 years were included in the analysis.…”
Section: Methodsmentioning
confidence: 99%